Does Surgical Stabilization of Lateral Compression‐type Pelvic Ring Fractures Decrease Patients' Pain, Reduce Narcotic Use, and Improve Mobilization?. Issue 6 (June 2016) - Hagen, Jennifer; Castillo, Renan; Dubina, Andrew; Gaski, Greg; Manson, Theodore T.; O'Toole, Robert V.
Abstract: Background: Debate remains over the role of surgical treatment in minimally displaced lateral compression (Young‐Burgess, LC, OTA 61‐B1/B2) pelvic ring injuries. Lateral compression type 1 (LC1) injuries are defined by an impaction fracture at the sacrum; type 2 (LC2) are defined by a fracture that extends through the posterior iliac wing at the level of the sacroiliac joint. Some believe that operative stabilization of these fractures limits pain and eases mobilization, but to our knowledge there are few controlled studies on the topic. Questions/purposes: (1) Does operative stabilization of LC1 and LC2 pelvic fractures decrease patients' narcotic use and lower their visual analog scale pain scores? (2) Does stabilization allow patients to mobilize earlier with physical therapy? Methods: This retrospective study of LC1 and LC2 fractures evaluated patients treated definitively at one institution from 2007 to 2013. All patients treated surgically, all nonoperative LC2, and all nonoperative LC1 fractures with complete sacral injury were included. In general, LC1 or LC2 fractures with greater than 10 mm of displacement and/or sagittal/axial plane deformity on static radiographs were treated surgically. One hundred fifty‐eight patients in the LC1 group (107 [of 697 screened] nonoperative, 51 surgical) and 123 patients in the LC2 group (78 nonoperative, 45 surgical) met inclusion criteria. The surgical and nonoperative groups were matched for fracture type. To account for differences between patients treated surgically and nonoperatively, we used propensity modeling techniques incorporating treatment predictors. Propensity scores demonstrated good overlap and were used as part of multiple variable regression models to account for selection bias between the surgically treated and nonoperative groups. Patient‐reported pain scores and narcotic administration were tallied in 24‐hour increments during the first 24 hours of hospitalization, at 48 hours after intervention, and in the 24 hours before discharge. Time from intervention to mobilization out of bed was recorded; intervention was defined as the date of definitive surgical intervention or the day the surgeon determined the patient would be treated without surgery. Results: There was no difference in the narcotics distributed to any of the groups with the exception that the patients with surgically treated LC2 fractures used, on average (mean [95% confidence interval]) 40.2 (−72.9 to −7.6) mg morphine less at the 48‐hour mark (p = 0.016). In general, there were no differences between the groups' pain scores. The surgically treated patients with LC1 fractures mobilized 1.7 (−3.3 to −0.01) days earlier (p = 0.034) than their nonoperative counterparts. There was no difference in the LC2 cohort in terms of time to mobilization between those treated with and without surgery. Conclusions: There were few differences in pain scores and morphine use between the surgical and nonoperative groups, and the differences observed likely were not clinically important. We found no evidence that surgical stabilization of certain LC1 and LC2 pelvic fractures improves patients' pain, decreases their narcotic use, and improves time to mobilization. A randomized trial of patients with similar fractures and similar degrees initial displacement would help remove some of the confounders present in this study. Level of Evidence: Level III, therapeutic study.